Gastrointestinal perforation in light chain amyloidosis in the era of novel agent therapy – a case series and review of the literature. (2nd January 2018) - Shaulov, Adir; Avivi, Irit; Cohen, Yael; Duek, Adrian; Leiba, Merav; Gatt, Moshe E.
Abstract: Gastrointestinal (GI) perforation is remarkably rare in patients with light chain (AL) amyloidosis and has not yet been reported in patients with AL amyloidosis treated with novel agents. Only 24 cases of GI perforation have previously been reported in the setting of AL amyloidosis of which 15 had available information in English. All 15 did not receive novel agent therapy and six died early after experiencing GI perforation. This study reports the characteristics and outcome of AL patients that developed GI perforation in the era of novel agent treatment. Seven patients were reviewed. In two patients, GI perforation was the presenting symptom of AL amyloidosis, whereas five patients developed GI perforations following initiation of an anti-AL therapy (three after bortezomib-based, 1 after lenalidomide-based and 1 after thalidomide-based therapy). All patients underwent surgery and survived the perforation. Treatment was renewed following surgery in six of seven patients, with no further GI complications. In conclusion, GI perforation in AL amyloidosis is rare and mostly reported after treatment initiation. Urgent surgery appears to be lifesaving and renewal of the anti-AL novel therapy appears to be safe, with no significant risk for re-perforation or GI toxicity. Prognosis in these patients is related to severity of the disease and response to therapy rather than the development of GI perforation.